Endoplasmic Reticulum-Mediated Protein Quality Control and Endoplasmic Reticulum-Associated Degradation Pathway Explain the Reduction of N-glycoprotein Level Under the Lead Stress - Du, Hong; Zheng, Canqi; Aslam, Muhmmad; Xie, Xihui; Wang, Wanna; Yang, Yingquan; Liu, Xiaojuan (Frontiers in Plant Science, 2021)
Different anthropogenic activities are resulting in the continuous increase of metal lead (Pb) in the environment and has adverse effects on living organism. Therefore, it is important to investigate the tolerance mechanism in model organism. Chlamydomonas reinhardtii is an important green eukaryotic model microalga for studying different kinds of biological questions. In this study, the responses of C. reinhardtii were revealed via a comprehensive approach including physiological, genomic, transcriptomic, glycomic and bioinformatic techniques. Physiological results showed that the growth rate and soluble protein content were significantly reduced under the high lead stress. And the results obtained from genomic and transcriptomic analysis presented that the endoplasmic reticulum-mediated protein quality control (ERQC) system and endoplasmic reticulum-associated degradation (ERAD) pathway were activated under the third day of high lead stress. The unique upregulated PDI genes on the ERQC system were proposed to be important for the protein level and protein quality control. The accumulation of specific N-glycans indicating that specific N-glycosylation of proteins might alter the biological functions of proteins to alleviate the Pb stress in alga, and /or lead to the degradation of incomplete/ mis-folded proteins. At the same time, it was observed that genes involved in each process of ERAD were upregulated, suggesting that the ERAD pathway was activated to assist the degradation of incomplete/ mis-folded proteins. Therefore, it is reasonable to speculate that the reduction of protein level under the high lead stress was related with the activated ERQC system and QRAD pathway. Our findings will provide a solid and reliable foundation and a proposed ERAD working model for further in-depth study of ERQC system and ERAD pathway under the Pb stress, and even other biotic and abiotic stresses.